Nature and Distribution of Cu and Pd Species in CuPd/TiO(2)–Na Bimetallic Catalysts for Glycerol Hydrodeoxygenation - Ardila A, Alba N. (ACS Omega, 2020)
[Image: see text] We demonstrated recently that CuPd/TiO(2)–Na bimetallic catalysts synthesized by sequential wet impregnation are active, selective, and stable for the hydrodeoxygenation (HDO) of glycerol into propylene glycol at low H(2) pressure. The present study reports on the nature and distribution of Cu and Pd surface species in CuPd/TiO(2)–Na bimetallic catalysts using different scanning transmission electron microscopy techniques that supply cluster-specific alloying details. In particular, we used atomic-resolution Z-contrast imaging, X-ray energy-dispersive spectroscopy, and electron energy-loss spectroscopy. We also include X-ray photoelectron spectroscopy results. Our analysis shows that the metallic nanoparticles adopt mainly five different structures according to how the Cu and Pd atoms coordinate among themselves: a homogeneous CuPd alloy structure (45–61%), a Cu shell/CuPd core (15–23%), a smaller number of particles formed by Cu on the surface and Pd in the nucleus (10–17%), and there are also nanoparticles formed only by Pd (4–7%) or by Cu (8–13%). We determined that there is a inhomogeneous distribution of Cu and Pd in the bimetallic nanoparticles, with Cu being predominant on the surface (between 76 and 90% of the total area analyzed for each particle). Most bimetallic nanoparticles have sizes below 6 nm, the Pd monometallic nanoparticles are in the 2–4 nm range, whereas the monometallic Cu nanoparticles are larger than 8 nm. Bimetallic nanoparticles with sizes smaller than 6–7 nm are fundamentally made up of Cu(0)–Pd(0) and Cu(1+)–Pd(0). The nanoparticles with sizes greater than 7 nm consist of Cu(2+) and Cu(2+)–Pd(2+). Our obtained results also help describe reports about the activation of HDO by Pd–Cu in the absence of H(2), an effect apparently not observed with other bimetallic systems.